2021
DOI: 10.3390/ijms221810028
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota and Gut–Brain Interplay in Selected Diseases of the Central Nervous System

Abstract: The gut microbiome has attracted increasing attention from researchers in recent years. The microbiota can have a specific and complex cross-talk with the host, particularly with the central nervous system (CNS), creating the so-called “gut–brain axis”. Communication between the gut, intestinal microbiota, and the brain involves the secretion of various metabolites such as short-chain fatty acids (SCFAs), structural components of bacteria, and signaling molecules. Moreover, an imbalance in the gut microbiota c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 155 publications
3
34
0
Order By: Relevance
“…RF predictive models also underlined the importance of the phylum Bacteroidota in migraine patients with IBS. Some studies showed similar results to ours, and decreased Firmicutes and increased Bacteroidetes in the gut microbiota were found in some central nervous system diseases, including patients with Alzheimer's disease (32), Parkinson's disease (33), multiple sclerosis (34), major depressive disorder, and autism spectrum disorder (35). However, some differences were observed between our study and previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…RF predictive models also underlined the importance of the phylum Bacteroidota in migraine patients with IBS. Some studies showed similar results to ours, and decreased Firmicutes and increased Bacteroidetes in the gut microbiota were found in some central nervous system diseases, including patients with Alzheimer's disease (32), Parkinson's disease (33), multiple sclerosis (34), major depressive disorder, and autism spectrum disorder (35). However, some differences were observed between our study and previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, many human disorders—including AD—are influenced by the dysregulation of miRNAs [ 169 , 170 ]. According to several studies, pathological circumstances alter the miRNA profile [ 171 , 172 ]. The dysregulation of miRNA expression in AD patients is supported by an increasing body of research.…”
Section: New Approachmentioning
confidence: 99%
“…Through interaction with enteroendocrine cells, SCFAs promote indirect signaling to the brain via the systemic circulation or vagal pathways by inducing the secretion of gut hormones such as glucagon-like peptide 1 (GLP1) and peptide YY (PYY), as well as γ-aminobutyric acid (GABA), and serotonin (5-HT). Finally, SCFAs also influence neuroinflammation by affecting glial cell morphology, continuously modulating microglia maturation, and also functioning to modulate the levels of neurotrophic factors, increasing neurogenesis, and improving neuronal homeostasis and function—known as gut microbiota-brain axis [ 187 , 199 ].…”
Section: Microbiota Mitochondria Intertwined Relationshipmentioning
confidence: 99%